PENINGKATAN KETERAMPILAN MEMBACA MELALUI MEDIA KARTU KATA BERBASIS POWERPOINT PADA ANAK KELOMPOK B DI TK AULIA SAMATA, KABUPATEN GOWA - Dewi, Asra; Asis, Asyriyah; Rauf, St. Muthia; Ilyas, Nurhidayah; Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early reading skills are a fundamental component of early childhood education. This study aimed to improve the early reading skills of Group B kindergarten students at TK Aulia Samata, Gowa Regency by using PowerPoint based word card media to improve letter recognition, phonemic awareness, and phoneme-grapheme correspondence. The study presented a multimedia supported method intended to engage children through interactive and graphically enriched content, acknowledging the shortcomings of traditional training. Three classroom sessions were used in a single cycle of the study, which used the Classroom Action Research (CAR) approach. PowerPoint presentations with animated word cards, visual cues, and auditory reinforcement that complemented the curriculum's thematic content were incorporated into each session. Four literacy indicators were used to gauge students progress through observations and performance evaluations using standardized rubrics.With 66.6% of participants achieving the